Familial retinoblastoma: fundus screening schedule impact and guideline proposal. A retrospective study - Rothschild, P-R (Nature Publishing Group, 2011)
AIMS: To assess if systematic fundus screening according to an ‘intensive' schedule alters ocular outcome and to propose fundus screening schedule guidelines for children related to a retinoblastoma patient. METHODS: For children with a positive family history of retinoblastoma, we perform fundus exams shortly after birth under general anaesthesia and then at regular intervals according to schedules based on the risk. Familial retinoblastoma cases seen at our institution from January 1995 to December 2004 were retrospectively classified as ‘screened' or ‘non-screened' (NS) and, among the ‘screened' patients, as ‘intensively screened' (IS) if screening matched our recommendations or ‘non-intensively screened' (S). Groups were compared by Fisher exact test for categorical variables and Kruskal–Wallis test for continuous variables. RESULTS: Among the 547 retinoblastoma patients managed at our institution during this period, 59 were familial cases. In all, 20 were in the NS group, 23 in the S group, and 16 in the IS group. The number of children enucleated was, respectively, 13, 2, and 0 (P<10(−4)); external beam radiation (EBRT) was required for, respectively, 6, 0, and 2 children (P<0.009). Chemotherapy burden and visual acuity were not significantly different between groups. CONCLUSION: An ‘intensive' fundus screening schedule decreased the need for enucleation and EBRT. Therefore, despite the heavy burden of the screening schedule, we recommend physicians and health-care professionals to better inform and refer children with a family history of retinoblastoma for genetic counselling and proper fundus screening in specialized centres.